Epistemic Understanding and Sound Reasoning Skills that Underlie Effective Democratic Engagement (In Factis Pax: Journal of Peace Education and Social Justice, 2010)
A voice in government, mostly through voting in elections, is commonly considered one of the hallmarks, if not the central activity, of citizenship in a democracy. However, the mere act of voting is a minimal expression of democracy. This point is made all too clear in countries with elections but without freedom of expression that cannot rightly be called democratic. What stands behind voting as a true democratic act is deliberation about for whom and what to vote. Such deliberation depends not just on the freedom to do so, but the ability to think critically and provide valid justifications of choices.